Sub-Saharan Africa financial sector challenges - Gulde, Anne-Marie.; Pattillo, Catherine A. (Catherine Anne); Christensen, Jakob; International Monetary Fund.; ProQuest (firma) ([Washintgon, D.C.] : International Monetary Fund, 2006)
Financial sectors in low-income sub-Saharan Africa (SSA) are among the world's least developed. In fact, assets in most low-income African countries are smaller than those held by a single medium-sized bank in an industrial country. The absence of deep, efficient financial markets seriously challenges policy making, hinders poverty alleviation, and constrains growth. This book argues that building efficient and sound financial sectors in SSA countries will improve Africa's economic prospects. Based on a review of the key features of financial systems, it discusses the main obstacles and challenges that financial structures pose for SSA economies and recommends steps that could address major shortcomings in implementing the reform agenda.
Includes bibliographical references (p. 47-49).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Finance -- Africa, Sub-Saharan.; Financial institutions -- Africa, Sub-Saharan.; Financial services industry -- Africa, Sub-Saharan.; Monetary policy -- Africa, Sub-Saharan.; elektronické knihy; electronic books